cAMP-stimulated Cl- secretion is increased by glucocorticoids and inhibited by bumetanide in semicircular canal duct epithelium - Pondugula, S. R.; Kampalli, S. B.; Wu, T.; Lisle, R. C.; Raveendran, N. N.; Harbidge, D. G.; Marcus, Daniel C. (My University, 2017)
The vestibular system controls the ion composition of its luminal fluid through several epithelial cell transport mechanisms under hormonal regulation. The semicircular canal duct (SCCD) epithelium has been shown to secrete Cl- under ß2-adrenergic stimulation. In the current study, we sought to determine the ion transporters involved in Cl- secretion and whether secretion is regulated by PKA and glucocorticoids.
Citation: Pondugula, S. R., Kampalli, S. B., Wu, T., Lisle, R. C., Raveendran, N. N., Harbidge, D. G., & Marcus, D. C. (2013). cAMP-stimulated Cl- secretion is increased by glucocorticoids and inhibited by bumetanide in semicircular canal duct epithelium. BMC Physiol, 13. doi:10.1186/1472-6793-13-6
Keywords: Chloride Secretion; Rat; Knockout Mouse; Primary Culture; Epithelium; Inner Ear